A critical appraisal of oil and gas dispute prone clauses: a case for Uganda's production sharing agreements /Samuel Munobe - Samuel , Munobe (2013)
To pursue exploration and production activities for her nascent oil and gas resources, Uganda negotiated and continues so to do and enter Production Sharing Agreements as the most appropriate relationship between herself and international hydrocarbon investor companies. Of course disputes in any relationship come about due to several reasons. In this research, potential dispute PSA clauses between investor oil companies and the State were identified for study. Library literature on dispute occurrence in the petroleum sector was confirmed by field interviews and observations carried out in Malaysia and Uganda for four months. This project sought to appraise the need for contractual lawyers and negotiators in the oil and gas field to be armed with adequate contract negotiation and drafting skills whose ultimate purpose was to enhance contract clause clarity and sanctity as dispute mitigation toolkits. Believing that disputes could be severed from contractual obligations, was synonymous to an attempt to planting boundary marks between the two concepts with a blackjack path trekking experience as such disputes could not be extricated from their founding contractual clauses. The roles of appropriate PSA pre-negotiation skills, proper contract drafting etiquettes and observance of the sanctity of contract doctrine were particularly relevant in dispute mitigation. An abundant wealth of knowledge on dispute resolution was however, available although not as such in the area of dispute prevention. This inquiry arose therefore, from the need to pay homage to the most sought for medical adage; "prevention is better than cure."